2012
DOI: 10.1007/s12263-012-0303-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in LEP and NPY genes modify the response to soluble fibre Plantago ovata husk intake on cardiovascular risk biomarkers

Abstract: The satiating effect of fibre consumption has been related to gut hormones, such as peptide YY and leptin. These peptides may also influence cardiovascular (CVD) risk biomarkers. Nevertheless, there is wide interindividual variation in metabolic responses to fibre consumption. The objective was to investigate differences in the effects of soluble fibre, in the form of Plantago ovata husk (Po-husk) treatment, on CVD risk biomarkers according to selected polymorphisms in genes related to satiety. The study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
13
0
1
Order By: Relevance
“…The relationship detected between the NPY rs16147 polymorphism and the effect of a low fat hypocaloric diet on CRP and IL-6 levels is reported by Crescenti et al (12) , who demonstrated a reduction of CRP in subjects with the AA genotype after 14 g day À1 of soluble fibre in the form of plantago ovata husk. This intervention with fibre added a low-fat diet for 8 weeks.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The relationship detected between the NPY rs16147 polymorphism and the effect of a low fat hypocaloric diet on CRP and IL-6 levels is reported by Crescenti et al (12) , who demonstrated a reduction of CRP in subjects with the AA genotype after 14 g day À1 of soluble fibre in the form of plantago ovata husk. This intervention with fibre added a low-fat diet for 8 weeks.…”
Section: Discussionmentioning
confidence: 61%
“…As far as we know, few studies have been designed aiming to explore the effect of rs16147 on metabolic response and weight change after a dietary intervention. Crescenti et al (12) reported that polymorphisms in NPY genes potentiate the response to plantago ovata husk in C-reactive protein (CRP) plasma concentration and systolic blood pressure. In another study (13) , NPY rs16147 genotypes were found to affect the change in abdominal adiposity in response to dietary intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Our study did not detect an interaction between genotype and response of inflammatory markers such as CRP. However, a relationship detected between the NPY rs16147 polymorphism and inflammatory markers (CRP and IL-6 levels) has been reported by Crescenti et al [11], too. These authors demonstrated a reduction in CRP levels in subjects with the AA genotype after 14 g/day of soluble fiber ( Plantago ovata husk) during a short-term intervention (8 weeks) with a low-fat diet.…”
Section: Discussionmentioning
confidence: 93%
“…In one study [10], the rs16147 variant of the NPY gene affected the change in abdominal adiposity in response to a hypocaloric dietary intervention. Moreover, in another design [11], it was reported that polymorphisms in the NPY gene modulate the response to Plantago ovata husk without a hypocaloric diet regarding C-reactive protein (CRP) plasma levels and systolic blood pressure. In a recent short-term intervention trial with a standard hypocaloric diet [12], it was shown that the rs16147 genotype affected anthropometric and biochemical parameters in response to a hypocaloric standard diet.…”
Section: Introductionmentioning
confidence: 99%
“…Crescenti et al (2013) em estudo que avaliou em indivíduos com hipercolesterolemia os efeitos de consumo de fibra solúvel sobre marcadores de risco cardiovascular e a influência de polimorfismos em genes relacionados às vias do controle do apetite e saciedade, visualizaram que o efeito benéfico da ingestão de fibras na redução da concentração de colesterol total mostrou-se variável de acordo com os genótipos do polimorfismo rs7799039 e sugerem que o SNP possa prejudicar os efeitos periféricos da leptina no metabolismo do colesterol(215).A concentração da leptina plasmática demonstra estar positivamente correlacionada com a adiposidade e possivelmente exerce influência sobre fatores de risco clássicos para a aterosclerose(216). A hiperleptinemia está associada com a maior calcificação de artérias coronarianas(217), agregação plaquetária (218) e o acúmulo de ésteres de colesterol em células espumosas(219).…”
unclassified